Project-Based Learning and Its Impact on Critical Thinking Skills in Primary Education - Yuni Misrahayu (Mandalika Institute, 2026)
Critical thinking is a fundamental skill that must be developed from the primary education level to support students’ problem-solving and decision-making abilities in the 21st century. However, learning practices in primary schools are still predominantly teacher-centered and emphasize memorization, which limits the development of higher-order thinking skills. This study aims to analyze the impact of Project-Based Learning (PjBL) on the critical thinking skills of primary school students. The research employed a qualitative approach using a literature study design. Data were collected from relevant national and international journal articles, academic books, and educational reports accessed through reputable databases. The selected literature was analyzed using qualitative content analysis to identify key patterns and themes related to the implementation of PjBL and its influence on students’ critical thinking skills. The findings indicate that Project-Based Learning has a positive impact on students’ critical thinking by engaging them in authentic problem-solving activities, inquiry-based learning, collaboration, and reflective processes. PjBL encourages students to analyze information, evaluate solutions, and connect learning content with real-life contexts. Overall, the study concludes that Project-Based Learning is an effective instructional approach for fostering critical thinking skills in primary education when supported by proper instructional design and teacher facilitation.